2014
DOI: 10.1167/iovs.14-15659
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Surface-Based Keratometry Compared With Scheimpflug Tomography-Based Total Corneal Astigmatism

Abstract: Total corneal astigmatism is overestimated by CASim-K in eyes with with-the-rule astigmatism and cannot be predicted safely in eyes that do not have with-the-rule astigmatism by anterior measurements only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
75
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 20 publications
13
75
0
1
Order By: Relevance
“…Anterior corneal astigmatism (AA) is the astigmatism value arising from the anterior corneal surface alone and calculated as the difference in simulated keratometry values (calculated using the standard keratometric index (1.3375) and the radius of anterior corneal curvature) between the steepest and the flattest meridians [1316]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anterior corneal astigmatism (AA) is the astigmatism value arising from the anterior corneal surface alone and calculated as the difference in simulated keratometry values (calculated using the standard keratometric index (1.3375) and the radius of anterior corneal curvature) between the steepest and the flattest meridians [1316]. …”
Section: Methodsmentioning
confidence: 99%
“…The posterior corneal astigmatism is defined as the difference in keratometry values between the flattest and steepest meridians, which were calculated using the radius of posterior corneal curvature and the refractive indices of the cornea (1.376) and aqueous humor (1.336) [1316]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We read with interest the article by Tonn et al 1 on corneal astigmatism. At the beginning of the article, the authors indicated that: ''Scheimpflug tomographers provide a map of the anterior chamber and therefore a more accurate model of the cornea, its thickness, and posterior surface.''…”
mentioning
confidence: 99%
“…Undoubtedly, we still have a long way to go to get truly reliable posterior corneal measurements and to determine the best way to analyze those data (there are several different complex vectorial methods available, which are not either straightforward or universally accepted) [5][6][7][8][9] ; but at least we have taken the first crucial steps in the right direction, and clinical studies such as the one performed by Tonn et al 1 will help us reach the goal of better results when implanting toric intraocular lenses. However, as Alpins et al 10 recently stated, posterior corneal astigmatism does not seem to be the only significant factor in the equation of final manifest refractive cylinder and noncorneal contributors likely include other sources of intraocular astigmatism (in pseudophakic eyes, IOL tilt or decentration) and processing in the visual cortex.…”
mentioning
confidence: 99%